MILP/MIQCP-Based Fully Automatic Method of Searching for Differential-Linear Distinguishers for SIMON-Like Ciphers - Yanyan Zhou; Senpeng Wang; Bin Hu (IET Information Security)
Differential-linear (DL) cryptanalysis is an important cryptanalytic method in cryptography and has received extensive attention from the cryptography community since its proposal by Langford and Hellman in 1994. At CT-RSA 2023, Bellini et al. introduced continuous difference propagations of XOR, rotation, and modulo-addition operations and proposed a fully automatic method using Mixed-Integer Linear Programing (MILP) and Mixed-Integer Quadratic Constraint Programing (MIQCP) techniques to search for DL distinguishers of Addition-Rotation-XOR (ARX) ciphers. In this paper, we propose continuous difference propagation of AND operation and construct an MILP/MIQCP-based fully automatic model of searching for DL distinguishers of SIMON-like ciphers. We apply the fully automatic model to all versions of SIMON and SIMECK. As a result, for SIMON, we find 13 and 14-round DL distinguishers of SIMON32, 15, 16, and 17-round DL distinguishers of SIMON48, 20-round DL distinguishers of SIMON64, 25 and 26-round DL distinguishers of SIMON96, 31 and 32-round DL distinguishers of SIMON128. For SIMECK, we find 14-round DL distinguishers of SIMECK32, 17 and 18-round DL distinguishers of SIMECK48, 22, 23, 24, and 25-round DL distinguishers of SIMECK64. As far as we know, our results are currently the best.